Genome-wide associations with longevity and reproductive traits in U.S. rangeland ewes - Smitchger, Jamin A.; Taylor, J. Bret; Mousel, Michelle R.; Schaub, Daniel; Thorne, Jacob W.; Becker, Gabrielle M.; Murdoch, Brenda M. (Frontiers in Genetics, 2024)
Improving ewe longevity is an important breeding and management goal, as death loss and early culling of mature ewes are economic burdens in the sheep industry. Ewe longevity can be improved by selecting for positive reproductive outcomes.; Hhowever, the breeding historical approaches for accomplishing this come with the challenge of recording a lifetime trait. Characterizing genetic factors underpinning ewe longevity and related traits could result in the development of genomic selection strategiestools to improve the stayability of sheep through early, informed selection of replacement ewes. Towards this aim, a genome-wide association study (GWAS) was performed to identify genetic markers associated with ewe longevity, reproductive, and production traits were evaluated through genome-wide association study (GWAS) to identify potential associations with markers on a high-density SNP array. Traits evaluated included longevity (i.e. length of time in the flock), parity and the lifetime number of lambs born, lambs born alive, lambs weaned, and weight of lambs weaned. Ewe records from previous studies were used. Specifically, Rambouillet (n = 480), Polypay (n = 404), Suffolk (n = 182) and Columbia (n = 64) breed ewes (N = 1,130) were analyzed against 503,617 SNPs in across-breed and within-breed GWAS conducted with the Bayesian- information and Linkage-disequilibrium Iteratively Nested Keyway (BLINK) model in R. The across-breed GWAS identified 25 genome-wide significant SNPs and the within-breed GWAS for Rambouillet, Polypay, and Suffolk ewes identified an additional 19 significant SNPs. The most significant markersresults were rs411309094 (13:22,467,143) associated with longevity in acrossbreed GWAS (P-value = 8.3E-13) and rs429525276 (2:148,398,336) associated with both longevity (P-value = 6.4E-15) and parity (P-value = 4.8E-15) in Rambouillet GWAS. Significant SNPs were identified within or in proximity (± 50 kb) of genes with known or proposed roles in reproduction, dentition, and the immune system. These genesGenes containing significant SNPs included ALPL,